2022
DOI: 10.2147/ccid.s359813
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Stimulators in Body Applications: A Review Focused on Poly-L-Lactic Acid (PLLA)

Abstract: The number of aesthetic procedures performed worldwide continues to grow together with an increase in the population seeking the restoration or preservation of a youthful appearance. Requests for non-surgical body rejuvenation are increasing. Patients are looking for safe and effective minimally invasive aesthetic procedures. Soft-tissue dermal fillers can meet these expectations. Based on the beneficial outcomes of these treatments in many facial areas, a new trend is developing to target body areas. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 127 publications
0
23
0
4
Order By: Relevance
“…Poly‐L‐Lactic Acid (PLLA) is a biocompatible, biodegradable, absorbable, immunologically inert, malleable, and easy‐to‐process polymeric synthetic polymer derived from plants that have been used in previous studies of synthetic suture materials. It was approved by the food and Drug Administration (FDA) in 2004 for the treatment of facial fat atrophy following immunodeficiency virus infection and in 2009 for nasolabial folds and other dermal wrinkles 8 . The volume‐expanding of PLLA post‐injection is caused by the thinner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly‐L‐Lactic Acid (PLLA) is a biocompatible, biodegradable, absorbable, immunologically inert, malleable, and easy‐to‐process polymeric synthetic polymer derived from plants that have been used in previous studies of synthetic suture materials. It was approved by the food and Drug Administration (FDA) in 2004 for the treatment of facial fat atrophy following immunodeficiency virus infection and in 2009 for nasolabial folds and other dermal wrinkles 8 . The volume‐expanding of PLLA post‐injection is caused by the thinner.…”
Section: Introductionmentioning
confidence: 99%
“…It was approved by the food and Drug Administration (FDA) in 2004 for the treatment of facial fat atrophy following immunodeficiency virus infection and in 2009 for nasolabial folds and other dermal wrinkles. 8 The volumeexpanding of PLLA post-injection is caused by the thinner. As the thinner is absorbed, the PLLA particles slowly degrade, promoting the formation of fibrous tissue and new collagen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its classic application in facial area, PLLA is currently used for volume increase, body contouring, sagging skin, scarring and fine line expansion in areas beyond the face such as neck and chest, buttocks, abdomen, arms, thighs, knees and hands. A recent survey reported that hip augmentation (42.4%) is the second most common use of PLLA in the USA, after HIV lipoatrophy (46.8%), which is enough to demonstrate the importance of PLLA in the field of body therapy [ 45 ].…”
Section: Advanced Biomaterials For Plastic Surgerymentioning
confidence: 99%
“…Sculptra® is becoming a popular option for noninvasive buttocks augmentation, particularly in individuals who lack sufficient amounts of donor fat for autologous fat transfer 34 . Numerous studies of varying evidentiary strengths have investigated PLLA buttocks injection for a range of purposes: improvement in skin laxity; reduction in the appearance of cellulite, scars, and striae; and overall augmentation/contouring 36 . One of the earliest reports of this novel use was by Lorenc in 2012, who reported positive outcomes with one vial of Sculptra® per buttock 37 .…”
Section: Off‐label Indicationsmentioning
confidence: 99%